THE SULTAN ADAM LAW IN THE PERSPECTIVE OF DUTCH EAST INDIES LEGAL POLITICS IN THE 18TH CENTURY IN THE FORMULATION OF POSITIVE LAW IN INDONESIA - Hasan, Ahmadi; Mu’ammar, Ali (Pascasarjana UIN ANTASARI Banjarmasin, 2020)
This research explores the Sultan Adam Law (UUSA) in the Kingdom of Banjar during the Dutch colonization and the reign of Sultan Adam (1825-1857). The UUSA, as a political law, reflects national law and the Shafi'i school of jurisprudence, despite being considered customary law. Islamic teachings, especially through the UUSA and the Book of Sabilal Muhtadin, are integrated into customary law due to literacy limitations. Sultan Adam, through structural governance reforms, implemented Islamic principles in Banjar society, with UUSA serving as a crucial foundation. This research highlights the contribution of UUSA in depicting the integration of Islamic law in the Kingdom of Banjar and recognizes its historical impact in the study of customary law.